Pengaruh Pola Komunikasi Organisasi Terhadap Motivasi Kerja Pegawai di Kantor Kecamatan Tajurhalang, Kabupaten Bogor - Ahlakania, Nabila (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Communication in an organization is carried out to drive activities within the organization. Therefore, the most important aspect that must be considered is employee motivation. Employee motivation indicators are measured using the Motivation Hierarchy Theory proposed by Abraham Maslow, there are five categories, namely physiological, safety or security, social, appreciation and self-actualization. This research aims to analyze the influence of organizational communication patterns on employee work motivation at the Tajurhalang District Office, Bogor Regency. This research used quantitative descriptive methods at the Tajurhalang District Office, Jl. Manunggal No.1 Tajurhalang, Bogor Regency. The data collection technique used is a nonprobability sampling technique with a sampling method, namely saturated samples. The respondents used as research samples were all 40 employees of the Tajurhalang subdistrict office, Bogor Regency. The results of this research show that the influence of the variable Organizational Communication Pattern (X) simultaneously on Work Motivation (Y) is 11.2%. In conclusion, organizational communication patterns have a significant effect on work motivation, with the results of the respondents' average scores being quite good.